The dual role of glucocorticoids in the breast cancer immune microenvironment: mechanisms and therapeutic implications - Liang, Bianping; Wang, Xinglan; Fu, Yunrui; Wang, Mingxue (Frontiers in Immunology, 2025)
Glucocorticoids (GCs), such as dexamethasone (Dex), are widely used in breast cancer treatment to alleviate chemotherapy-induced side effects. However, their immunomodulatory effects on the tumor microenvironment (TME) exhibit a dual nature. On one hand, Dex may delay tumor progression by suppressing pro-inflammatory cytokine release, modulating T-cell function, and inhibiting angiogenesis. On the other hand, Dex can promote the formation of an immunosuppressive TME by activating the glucocorticoid receptor (GR) signaling pathway, thereby accelerating breast cancer metastasis. This review summarizes the molecular mechanisms by which Dex influences breast cancer lung metastasis through its regulation of immune cells (e.g., T cells, B cells, myeloid cells), cytokine networks, and metabolic reprogramming in the TME. Additionally, potential strategies targeting GR or combining immunotherapy are discussed.Therefore, this mini review aims to elucidate the complex mechanisms of Dex in the breast cancer TME and ultimately guide the translation of mechanistic discoveries into clinical breakthroughs.